PRELMINARY ANTMICROBAL SCREENING OF SIXTY INDGENOUS PLANTS FROM KHAN DESHREGION, MAHARASHTRA - PATOLIE, S.S.; MAHAJAN, R.T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Total aqueous extract (TAE) of 60 indigenous plant species were screened for their in vitro antimicrobial activity against two bacterial species i.e. Bacillus subtilis and Escherichia coli and single fungus ie. Aspergillus nigar. The results from well diffusion method showed that of the 60 plants, 27 plants inhibited the growth of Bacillus subtilis, 14 plants against Escherichia coli and 19 plant extracts acted as antifungal against Aspergillus nigar. 11 plants showed a broad spectrum of antimicrobial activity whereas 32 plant extracts exhibited negligible activity. The Zone of inhibition of the TAE of plants was ranging from 5 to 15 mm. The results indicate that Allium Sativum Linn, Azadirachta indica A. Juss., Curcuma longa Linn and Tridex procumbens Linn possesses potential broad spectrum antimicrobial activity.